Shedding Light on NF-κB Functions in Cellular Organelles - Carrà, Giovanna; Avalle, Lidia; Seclì, Laura; Brancaccio, Mara; Morotti, Alessandro (Frontiers in Cell and Developmental Biology, 2022)
NF-κB is diffusely recognized as a transcriptional factor able to modulate the expression of vari-ous genes involved in a broad spectrum of cellular functions, including proliferation, survival and migration. NF-κB is, however, also acting outside the nucleus and beyond its ability to binds to DNA. NF-κB is indeed found to localize inside different cellular organelles, such as mi-tochondria, endoplasmic reticulum, Golgi and nucleoli, where it acts through different partners in mediating various biological functions. Here, we discuss the relationship linking NF-κB to the cellular organelles, and how this crosstalk between cellular organelles and NF-κB signalling may be evaluated for anticancer therapies.